Natural hosts and animal models for Rift Valley fever phlebovirus - Xu, Yuqing; Wang, Xiao; Jiang, Lu; Zhou, Yixuan; Liu, Yihan; Wang, Fei; Zhang, Leiliang (Frontiers in Veterinary Science, 2023)
Rift Valley fever phlebovirus (RVFV) is a zoonotic mosquito-transmitted arbovirus, presenting a serious threat to humans and animals. Susceptible hosts are of great significance for the prevention of RVFV. Appropriate animal models are helpful to better understand the onset and development of diseases, as well as the control measures and vaccine research. This review focuses on the role of animal hosts in the maintenance of the virus, and summarizes the host range of RVFV. We list some common animal models in the process of RVFV research, which would provide some important insights into the prevention and treatment of RVFV, as well as the study of Rift Valley fever (RVF) pathogenesis and vaccines.